HPV vaccines and lupus: current approaches towards preventing adverse immune cross-reactivity - Nicola L. Bragazzi; Charlie Bridgewood; Kassem Sharif; Mohamad Kamal; Howard Amital; Abdulla Watad; Yehuda Shoenfeld (Taylor & Francis Group, 2019)
Introduction: If not properly treated, human papillomavirus (HPV) infection may evolve from a common sexually transmitted disease to genital warts and cervical cancer. Various prophylactic HPV vaccines (HPVv), approved to reduce the incidence of the infection, have been found to be effective and safe; however, accounts of post-vaccination autoimmune phenomena, including systemic lupus erythematosus (SLE), have been reported in genetically susceptible individuals. Areas covered: Infectious agents play a role in breaking the immunologic tolerance to self-antigens, resulting in autoimmune events. There is molecular evidence supporting the involvement of HPV in SLE, with a high prevalence of L1 HPV peptide homology to proteins being associated with SLE. Therefore, approaches in vaccine preparations aiming to prevent adverse immune cross-reactivity are sought. Performing a broad search of the literature, we review the association between SLE, HPV, and HPVv, with a focus on the mechanisms of molecular mimicry and cross-reactivity, and the approaches currently being elaborated towards preventing such phenomena. Expert commentary: The advantages of using low-similarity peptide antigens may be two-fold, abolishing the risk of cross-reactivity and eliminating the vaccine adjuvantation procedure. Vaccines based on pathogen unique sequences would provide effective vaccine preparation while curbing the risk for the human host.